Quality and antioxidant properties of whole and fresh cut 'Cherry' peppers during storage at 10 °C - Avalos Llano, Karina Roxana (2009)
Changes on quality and antioxidant properties of whole and fresh cut (without the core) peppers (Capsicum annuum, L. cv. ‘Cherry’), stored for 10 days at 10ºC in PET trays covered with PVC film were studied. During the storage their general appearance, fungal decay, color, respiration rate,sugar content and firmness were evaluated. Changes on carotenoids, total phenols, ascorbic acid and antioxidant capacity were also studied. Immediately after cutting and throughout the storage, an increase in respiration rate was found. No differences in color evolution were observed during storage between whole and fresh cut fruits. There were no differences in firmness, total sugars and carotenoids between whole and cut fruits either. Total phenols, ascorbic acid and antioxidant capacity did not change largely in both intact and without core peppers during the experiences. However at the end of the storage period (10 days), whole pepper fruit displayed good general appearance and overall higher quality than de-cored fruit. Results suggest that Cherry peppers could be marketed as fresh-cut peppers in the type of without core fruits, although they would be only stored for 6-7 days at 10ºC.